Diversity in the Child Criminal Justice System - Sartika Intaning Pradhani (Jurnal Cita Hukum, 2017)
The Child Criminal Justice System in practice, the child as a victim of sexual violence does not always feel its justice being reversed because the diversion process involving the community, the police, the social department, and the parties concerned does not always have a victim's perspective. The absence of a victim's perspective in resolving the issue of sexual violence through diversities makes restorative justice incapable of restoring and fulfilling justice for child victims of sexual violence compared to the criminal justice system in general because diversity is unable to bridge the gap between the challenges faced by victims and the help available to victims. Legal protection of child victims of crime, especially crimes against morality, with child offenders under the Criminal Justice System which must prioritize the approach of Restorative Justice by guaranteeing the rights of child victims to the efforts of medical rehabilitation and social rehabilitation both inside and outside the institution; assurance of safety, whether physical, mental, or social; and ease in obtaining information about case development through diversion. Sistem Peradilan Pidana Anak pada praktiknya, anak sebagai korban kekerasan seksual tidak selalu merasakan keadilannya dikemalikan karena proses diversi yang melibatkan masyarakat, polisi, departemen sosial, dan para pihak terkait tidak selalu memiliki perspektif korban. Ketiadaan perspektif korban dalam penyelesaian permasalahan kekerasan seksual melalui diversi membuat keadilan restoratif tidak mampu mengembalikan dan memenuhi keadilan bagi anak korban kekerasan seksual dibandingkan dengan sistem peradilan pidana secara umum karena diversi tidak mampu untuk menjembatani jurang antara tantangan yang dihadapi oleh para korban dan pertolongan yang tersedia untuk para korban. Perlindungan hukum terhadap anak korban kejahatan, khususnya kejahatan terhadap kesusilaan, dengan pelaku anak menurut Sistem Peradilan Pidana Anak yang wajib mengutamakan pendekatan Keadilan Restoratif dengan memberikan jaminan hak anak korban terhadap upaya rehabilitasi medis dan rehabilitasi sosial, baik di dalam lembaga maupun di luar lembaga; jaminan keselamatan, baik fisik, mental, maupun sosial; dan kemudahan dalam mendapatkan informasi mengenai perkembangan perkara melalui diversi. DOI: 10.15408/jch.v5i1.6575